2017
DOI: 10.1080/13880209.2017.1309553
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumour potential of camel’s milk against hepatocellular carcinoma in rats and its improvement of cisplatin renal side effects

Abstract: Context: Camel milk (CM) is recommended for liver disease patients in Egypt for a strong belief that it has a curative effect.Objective: The effect of consumption of CM with or without chemotherapeutic drug cisplatin was evaluated on induced hepatocarcinogenesis in rats.Materials and methods: Wistar male rats (56) were divided into eight groups (7 rats each). Group I was control. Hepatocarcinogenesis was initiated by a single dose of intraperitoneal injection of diethylnitrosamine (DENA) (200 mg/kg BW) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(36 reference statements)
0
8
0
1
Order By: Relevance
“…In parallel, animal experimental data have also demonstrated the inhibitory potential of CM and its constituents against various forms of cancer [77][78][79]. Interestingly, CM has been shown to interfere with the expression of cancer-related mediators at both gene and protein levels [69].…”
Section: Nutritional Components (Macronutrients and Micronutrients)mentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, animal experimental data have also demonstrated the inhibitory potential of CM and its constituents against various forms of cancer [77][78][79]. Interestingly, CM has been shown to interfere with the expression of cancer-related mediators at both gene and protein levels [69].…”
Section: Nutritional Components (Macronutrients and Micronutrients)mentioning
confidence: 99%
“…Various in vitro studies have revealed the inhibitory effects of CM and its constituents against various forms of cancer, apparently through induction of apoptotic pathways [ 2 , 12 , 69 , 72 , 73 , 74 , 75 , 76 ]. In parallel, animal experimental data have also demonstrated the inhibitory potential of CM and its constituents against various forms of cancer [ 77 , 78 , 79 ]. Interestingly, CM has been shown to interfere with the expression of cancer-related mediators at both gene and protein levels [ 69 ].…”
Section: Brief Overview Of Camel Milk (Cm) Componentsmentioning
confidence: 99%
“…Altogether, the inhibitory effect of camel milk and its exosome on cancerous cells is due to the induction of apoptosis and antioxidative effects. It was experimentally proved that cisplatin in combination with camel milk inhibited hepatocarcinogenesis in rats after initiating cancer-inducing diethylnitrosamine, which is again due to the antioxidant effect of camel milk [ 122 ].…”
Section: Camel Milk As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…It contains a variety of protective proteins like casein, lactoferrin, lysozymes, lactoperoxidase, vitamin C, serum albumin, immunoglobulins (4) which in turn provide camel milk with potential health benefits. There are several reports about the medicinal effects of camel milk and its ingredients; antioxidative, antihypertensive, antimicrobial, and anticancer effects (5)(6)(7)(8). A previous study showed that camel milk might be recommended as a nutrition protein source for children have allergy to cow milk (9).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing more effective treatment strategies are of paramount importance to prevent or retard the hepatic alterations induced due to hepatocarcinogenesis. In previous studies revealed the antitumor effects of camel milk on chemically-induced hepatocellular carcinoma (7,32). Therefore, our study was designed to investigate the potential antitumor effects of a camel milk constituent (purified total immunoglobulin IgG [CM-IgG]) on DENA-induced hepatocarcinoma in rats.…”
Section: Introductionmentioning
confidence: 99%